Postoperative management of patients after laparoscopic cholecystectomy - Bogomaz, Volodymyr; Starodub, Tetiana (Journal of Education, Health and Sport, 2025)
Introduction and purpose: laparoscopic cholecystectomy is the standard treatment for symptomatic cholelithiasis; however, a substantial proportion of patients continue to experience abdominal pain and dyspeptic symptoms after surgery, which requires structured postoperative follow-up. Telemedicine is increasingly used for postoperative monitoring, but data on its effectiveness and safety after cholecystectomy remain limited. The purpose of this study was to evaluate the effectiveness and safety of telemedicine-based postoperative follow-up compared with conventional outpatient care. Material and method: this prospective study included 156 patients who underwent laparoscopic cholecystectomy for gallstone disease in two medical centers in Ukraine during 2023–2025. Patients were allocated into a telemedicine follow-up group (n = 77) and a conventional outpatient follow-up group (n = 79). Postoperative assessment was conducted at 1 and 6 months using a structured questionnaire evaluating overall well-being, abdominal pain, dyspeptic symptoms, physical activity, and appetite. Results: one month after surgery, symptoms were reported by 51.9% of patients, including abdominal pain in 21.2% of cases, predominantly mild or moderate. The most common complaints were abdominal bloating, heartburn, postprandial fullness, nausea after fatty food intake, and loose stools. At six months, the proportion of symptomatic patients decreased to 34.0%, and abdominal pain persisted in 9.6% of patients, mainly mild. Dyspeptic symptoms became less frequent. No postoperative complications or readmissions were recorded, and no significant differences were observed between follow-up groups (p > 0.05). Conclusions: telemedicine-based postoperative monitoring after laparoscopic cholecystectomy provides clinical outcomes comparable to conventional outpatient follow-up and may be considered an appropriate option for routine follow-up after uncomplicated surgery.